Overview of trygleseride level on coffee consumption - Amellya Octifani; Tarisa Suci Novianti; Farida Anwari; Arif Rahman Nurdianto; Fery Setiawan; Rizal Fauzi Nurdianto (Jurnal Teknologi Laboratorium)
Coffee is a drink that is commonly consumed by Indonesian people. Coffee contains caffeine, cafestol, and kahweol which can increase lipid levels, including increasing triglyceride levels. Triglycerides are substances consisting of glycerol linked to fatty acid groups. The purpose of this study was to describe blood triglyceride levels in coffee addict students at Anwar Medika University using the GPO-PAP method. This study uses a quantitative descriptive design with a cross-sectional survey approach. This research was conducted in May 2023. The research sample consisted of 48 samples which were determined using a purposive sampling technique which was taken at random. The univariate analysis used is the distribution of frequencies and percentages which describe the presentation of data for one variable. This research test obtained an average triglyceride level of 158.7 mg/dl. Based on age category, maximum triglyceride levels were 204.73 mg/dl with an average of 152.26 mg/dl. Based on lifestyle, the maximum triglyceride level is 189.93 mg/dl with an average of 166.43 mg/dl. Based on the frequency of coffee consumption, the maximum triglyceride level is 160.64 mg/dl with an average of 158.51 mg/dl. Based on physical activity, the maximum triglyceride level is 173.88 mg/dl with an average of 160.60 mg/dl. Based on the type of coffee consumed, the maximum triglyceride level was 166.76 mg/dl with an average of 164.57 mg/dl. So, it can be concluded that excessive coffee consumption can increase triglyceride levels in the body.